2013
DOI: 10.1021/pr400738a
|View full text |Cite
|
Sign up to set email alerts
|

Dual LC–MS Platform for High-Throughput Proteome Analysis

Abstract: We describe a dual-column interface for parallel chromatography to improve throughput during LC-MS experimentation. The system employs a high-voltage switch to operate two capillary column/nanospray emitters fixed at the MS orifice. Sequentially loading one column while operating the second nearly doubles the LC-MS duty cycle. Given the innate run-to-run variation of a nanospray LC-MS (12% RSD peak area; 2% retention time), the intercolumn variability of the platform showed no meaningful difference for proteom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(41 citation statements)
references
References 30 publications
0
38
0
Order By: Relevance
“…To circumvent this problem, we separated re-equilibration time from total analysis time using the multiple column system. It is important to note that our LC system consists of the least equipment to perform the analytical and wash gradient compared to previous reports (Korfmacher et al 1999;Cass et al 2001;Oertel et al 2002;Orton et al 2013;Lee et al 2015;Patel et al 2016). This is simple and easy-to-use for most LC/MS users.…”
Section: Chromatographic Separationmentioning
confidence: 99%
See 1 more Smart Citation
“…To circumvent this problem, we separated re-equilibration time from total analysis time using the multiple column system. It is important to note that our LC system consists of the least equipment to perform the analytical and wash gradient compared to previous reports (Korfmacher et al 1999;Cass et al 2001;Oertel et al 2002;Orton et al 2013;Lee et al 2015;Patel et al 2016). This is simple and easy-to-use for most LC/MS users.…”
Section: Chromatographic Separationmentioning
confidence: 99%
“…Several studies have reported good chromatographic separation; however, these methods require long times to separate nucleosides (Djukovic et al 2010;Cho et al 2009;Struck et al 2011;Lee et al 2004). Rodríguez-Gonzalo et al (2016) reported an analytical method that quickly and simultaneously determined nucleosides; however, this method has not been used to study significant cancer biomarkers or cellular stress markers, such as m 5 C, Cm, and m 2 2 G. (Nakano et al 1993;Djukovic et al 2010;Cho et al 2009;Chan et al 2010) m 3 C Alkylating stress (Chan et al 2015) m 5 C Oxidative stress, replication stress (Chan et al 2010(Chan et al , 2012 Cm Oxidative stress, replication stress (Chan et al 2010) s 2 C Interference with codon-anti-codon interaction (Agris 2015) m 5 U Replication stress (Endres et al 2015) Ψ Gastric cancer, intestinal cancer, lung cancer, AIDS, leukemia, lymphoma (Nakano et al 1993;Itoh et al 1992) (Korfmacher et al 1999;Cass et al 2001;Oertel et al 2002;Orton et al 2013;Lee et al 2015;Patel et al 2016). This approach is helpful for reducing the total run time without sacrificing chromatographic separation, as using multiple columns reduces separation and wash times.…”
Section: Introductionmentioning
confidence: 99%
“…Our concept aimed to maximize robustness: two fixed columns mounted side by side (Figure A), operated by two LC pumps. With pencil and paper, we drafted a six‐port valve configuration to divert flow between two LC pumps (one for sample loading and the other to run gradients) . Relay contacts from the HPLC system controlled the switch valve and alternated high‐voltage (HV) power supply to one of the two capillary columns.…”
Section: Case Study: Overcoming Limitations Of Lc‐msmentioning
confidence: 99%
“…Köcher et al demonstrated that the peak capacity is increased with increasing gradient time and analytical column length, and the increased peak capacity leads to improved detection of low abundant proteins. [16][17][18][19][20] Livesay et al reported a highthroughput LC system that utilized four columns. [10][11][12][13][14] Shi et al reported that the utilization of a long gradient (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…300 min) on a long packed capillary column (75 μm × 150 cm) can increase the sensitivity of LC-MRM experiments dramatically, achieving 3 times more multiplexing capacity than conventional LC-MRM and LOQ of 10 ng mL −1 without depleting abundant proteins and fractionating samples. 19 Utilizing only one additional switching valve, the system successfully provided a near double LC-MS/MS duty cycle. Despite dramatic improvement in sensitivity, the use of a long and narrow column with a long gradient in the UHPLC system requires a long lead time for sufficient column equilibration before the next experiment.…”
Section: Introductionmentioning
confidence: 99%